The Effects of Acupressure and Acupuncture as Natural Induction Methods for Spontaneous Labor: A Systematic Review - Ertitawati Siregar; Lucky Herawati; Runjati Runjati; Maya Erisna (International Journal of Nursing and Health Services (IJNHS), 2020)
.  Induction of labor is high all over the world. Pharmacological and mechanical labor induction is one of the most frequent medical actions in midwifery services across the world. This systematic review aims to analyze the effectiveness of acupressure and acupuncture on the induction of spontaneous labor. Articles were retrieved from PubMed, Google Scholar, and ScienceDirect until March 3rd, 2020. Only articles published from 2010 to 2020 were included. Keywords used consisted of “acupuncture,” “acupressure for induction of labor,” “acupressure for initiation of labor,” “term pregnancy”.  Articles were filtered using inclusion criteria. The literature search resulted in 1.365 articles. A total of 9 articles (5 acupressure and 4 acupuncture studies) were included for review. The total number of participants was 1,656 people. One study suggested that acupressure was effective in increasing cervical maturation. Two studies (1 acupressure and 1 acupuncture) stated that it was raised the frequency of initiation of spontaneous labor. One study showed that acupuncture reduced the need for medical induction. Other studies showed no significant effect. Overall, studies demonstrated a positive effect of acupressure and acupuncture on cervical maturation and increasing the frequency of initiations of spontaneous labor. Besides, it may reduce the need for medical induction. Further investigations are needed